(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the theoretical foundations, content, principles, and development stages of the continuous education system. It highlights issues related to integration between educational levels and improvement based on modern pedagogical approaches. The study also explores the role of continuous education in the global educational space, the impact of innovative technologies, and prospects for the development of the national education model. The findings contribute to the development of scientific recommendations for the effective organization of continuous education.